Importance sampling for Markovian tandem queues using subsolutions: exploring the possibilities. (December 2021) - Buijsrogge, Anne; de Boer, Pieter-Tjerk; Scheinhardt, Werner R W
We consider importance sampling simulation for estimating the probability of reaching large total number of customers in anM | M | 1 tandem queue, during a busy cycle of the system. Our main result is a procedure for obtaining a family of asymptotically efficient changes of measure based on subsolutions. We explicitly show these families for two-node tandem queues and we find that there exist more asymptotically efficient changes of measure based on subsolutions than currently available in literature.